Analisa Kadar Protein Jamur Alam yang Dominan Dikonsumsi Masyarakat Lokal di Kabupaten Lanny Jaya - Sarah Yigibalom; Supeni Sufaati; Vita Purnamasari (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
Wild edible mushroom is one of the Indonesian biodiversity richness. However, only a few of them had been utilized by human. Lanny Jaya is regency that located in the highland of Papua in which the community depend much on the natural resources to fulfill their basic needs of life. This study has aim to collect and analyze protein content of wild edible mushroom which was commonly consumed by local communities at Lanny Jaya. Collected samples were described based on habitat and morphological characters such as the shape, size and color of the mushroom, then protein were analyzed by Kjeldahl method. The result showed that there was 4 (four) species of wild edible mushroom that commonly consume in Lanny Jaya, namely: Obon, Punawi, Nambu and Enggambi. The highest protein content was Obon (35,03%), followed by Punawi (31,81%), and Nambu (28%), while the last was Enggambi (18,91%). Those wild edible mushroom can be used as an alternative protein source for the local people especially in remote areas. Key words: protein, fungi, edible, local people, Lanny Jaya.